Responding to Research Misconduct: A Primer for LIS Professionals. Issue 3 (3rd July 2019) - Herr, Melody
ABSTRACT: Falsification, fabrication, plagiarism, and other forms of misconduct undermine the foundation of science – trust in the integrity of researchers and their reported results. As research team members, therefore, library and information science (LIS) professionals share responsibility for addressing research misconduct. Intended as a primer, this article defines misconduct, discusses it causes, and notes its consequences. The article then empowers LIS professionals with a set of strategies, escalating from gathering information, to engaging in conversation, to submitting formal allegations, to respond effectively when they suspect or detect misconduct.